2017
DOI: 10.1590/1678-457x.38416
|View full text |Cite
|
Sign up to set email alerts
|

Coating with chitosan film of sea bream (Sparus aurata) fillets: determining shelf life in refrigerator conditions

Abstract: In the investigate, we objectived to assess the effect of coating with chitosan film on the shelf life. To this end, skinless sea bream fillets were separated as control group (C), vacuum packed (VP) and coated with chitosan film and vacuum packed (CF+VP). Samples of each group were periodically analyzed for microbiological [Total mesophilic aerobic count (TMAc) and Total psychrophilic aerobic count (TPAc)] and physicochemical [pH, Total volatile basic nitrogen (TVB-N), Thiobarbituric acid (TBA) and Trimethyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…These differences may be attributed to the antimicrobial activity of chitosan microparticles, contributing to the reduction of bacterial population and decreasing the capacity of microorganisms for oxidative deamination of non-protein nitrogen compounds. Similar results were reported for chitosan treated fillets of salmon, sea bream and sea bass (Alves et al, 2018;Izci et al, 2017;Li et al, 2016). In a study carried out on silver carp, it is Table 1.…”
Section: Changes In Total Volatile Basic Nitrogensupporting
confidence: 80%
See 1 more Smart Citation
“…These differences may be attributed to the antimicrobial activity of chitosan microparticles, contributing to the reduction of bacterial population and decreasing the capacity of microorganisms for oxidative deamination of non-protein nitrogen compounds. Similar results were reported for chitosan treated fillets of salmon, sea bream and sea bass (Alves et al, 2018;Izci et al, 2017;Li et al, 2016). In a study carried out on silver carp, it is Table 1.…”
Section: Changes In Total Volatile Basic Nitrogensupporting
confidence: 80%
“…Particular interest has been focused on the potential application of natural anti-microbial and antioxidant additives, such as essential oils, limonene, allyl isothiocyanate and light salting on the shelf-life of gilthead sea bream (Attouchi & Sadok, 2012;Giarratana et al, 2016;Goulas & Kontominas, 2007;Muscolino et al, 2016). Among natural additives, chitosan is being widely used because of its efficiency in improving the product shelf-life (Izci, Ekici, & Günlü, 2017;Küçükgülmez, Kadak, & Gӧkçin, 2013a;Li, Jiang, Li, & Hu, 2016). It is also appreciated for its safety and easy use (Qiu, Chen, Liu, & Yang, 2014;Yu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Chitosan shows outstanding antimicrobial activity against Gram‐positive bacteria and Gram‐negative bacteria because its amino groups can react with the negatively charged microbial cell membranes and ultimately cause a rupture of bacterial membrane 8,9 . Levent et al reported that the shelf life of sea bream wrapped in chitosan film was extended by 10 days due to the antimicrobial activity of chitosan 10 . Apart from antimicrobial activity, chitosan also possesses antioxidant activity as its amino and hydroxyl groups can react with free radicals 11 .…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Levent et al reported that the shelf life of sea bream wrapped in chitosan film was extended by 10 days due to the antimicrobial activity of chitosan. 10 Apart from antimicrobial activity, chitosan also possesses antioxidant activity as its amino and hydroxyl groups can react with free radicals. 11 Therefore, chitosan is a promising biopolymer for active food packaging.…”
Section: Introductionmentioning
confidence: 99%